Field Measurement of Beef Pen Manure Methane and Nitrous Oxide Reveals a Surprise for Inventory Calculations. Issue 3 (1st May 2015) - Redding, M. R.; Devereux, J.; Phillips, F.; Lewis, R.; Naylor, T.; Kearton, T.; Hill, C. J.; Weidemann, S.
Abstract : Few data exist on direct greenhouse gas emissions from pen manure at beef feedlots. However, emission inventories attempt to account for these emissions. This study used a large chamber to isolate N2 O and CH4 emissions from pen manure at two Australian commercial beef feedlots (stocking densities, 13–27 m 2 head) and related these emissions to a range of potential emission control factors, including masses and concentrations of volatile solids, NO3 −, total N, NH4 +, and organic C (OC), and additional factors such as total manure mass, cattle numbers, manure pack depth and density, temperature, and moisture content. Mean measured pen N2 O emissions were 0.428 kg ha −1 d −1 (95% confidence interval [CI], 0.252–0.691) and 0.00405 kg ha −1 d −1 (95% CI, 0.00114–0.0110) for the northern and southern feedlots, respectively. Mean measured CH4 emission was 0.236 kg ha −1 d −1 (95% CI, 0.163–0.332) for the northern feedlot and 3.93 kg ha −1 d −1 (95% CI, 2.58–5.81) for the southern feedlot. Nitrous oxide emission increased with density, pH, temperature, and manure mass, whereas negative relationships were evident with moisture and OC. Strong relationships were not evident between N2 O emission and masses or concentrations of NO3 − or total N in the manure. This is significant because many standard inventory calculation protocols predict N2 O emissions using the mass of N excreted by the animal.